2015
DOI: 10.11646/phytotaxa.230.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Two new Navicula species (Bacillariophyceae) from Western Europe

Abstract: During a survey of some springs in the French Central Massif, a new Navicula species (Bacillariophyceae) was found: Navicula sanctamargaritae Beauger sp. nov. A second new Navicula species was observed during a routine biomonitoring project in Flanders: Navicula flandriae Van de Vijver & A.Mertens sp. nov.. The new species are formally described using light and scanning electron microscopy. Both species present a unique set of morphological characters including the structure of the central raphe endings, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 7 publications
3
29
0
Order By: Relevance
“…The LM and SEM observations ( Fig. 6k-p) were consistent with those given by Beauger et al (2015). Navicula flandriae was accompanied by Pleurosira laevis var.…”
Section: Comparison the New Species With Morphologically Related Taxasupporting
confidence: 89%
See 2 more Smart Citations
“…The LM and SEM observations ( Fig. 6k-p) were consistent with those given by Beauger et al (2015). Navicula flandriae was accompanied by Pleurosira laevis var.…”
Section: Comparison the New Species With Morphologically Related Taxasupporting
confidence: 89%
“…6a-j). According to Van de Vijver and Mertens in Beauger et al (2015), the valves are 35-65 μm long, 7.0-9.5 μm wide with 12-13 striae per 10 μm. The specimens that were found in Poland were characterised by a higher stria density in both the smaller and larger specimens.…”
Section: Comparison the New Species With Morphologically Related Taxamentioning
confidence: 99%
See 1 more Smart Citation
“…While observing samples from freshwater sources in the Auvergne region (Beauger et al 2015(Beauger et al , 2016(Beauger et al , 2019 we have found a common freshwater Cocconeis that we have initially identified as an unknown species, until a deeper search in the literature led us to the name Cocconeis rouxii. Since there is no clear understanding or illustrations of this species in the literature, we provide here a detailed historical bibliographic revision as well as a wide morphological account of the variability of this species with LM and SEM illustrations.…”
Section: Introductionmentioning
confidence: 99%
“…The first studies conducted on springs from the Massif Central underlined the high algae biodiversity (Héribaud 1893;Chaouite 1987;Chaouite and Romagoux 1989;Tudesque 1996;Cordonnier 2008). The first survey performed in 2014-2015 in order to estimate the biodiversity in different mineral springs more or less impacted by human activities, revealed the presence of several new taxa, including some recently described such as Navicula sanctamargaritae Beauger in Beauger et al (2015) and Sellaphora labernardierei Beauger, C.E. Wetzel et Ector in Beauger et al (2016).…”
Section: Introductionmentioning
confidence: 99%